Pembuatan Aplikasi Virtual Tour 360 Sebagai Media Dalam Pengenalan Lingkungan Kampus Di Universitas Papua Menggunakan Unity 3D Engine: Making a 360 Virtual Tour Application as a Media for Introducing the Campus Environment at the University of Papua Using Unity 3D Engine - Yosia Artahsasta; Marlinda Sanglise; Julius Panda Putra Naibaho (JISTECH: Journal of Information Science and Technology, 2024)
Introduction to the campus environment for new students in carrying outPKKMB. At the time of Covid-19, many new students at the University ofPapua did online PKKMB without being familiar with the environment andthe faculty building for new students, whereas after the Covid-19 outbreaksubsided there were still students who did not know the faculty building. Byusing virtual reality tour technology, which can be accessed via smartphone,new students can familiarize themselves with the campus environment whendoing PKKMB, where new students can get to know the new environment verywell and know the location of each faculty building where they will study.Therefore, the author wants to create an application that can help newstudents at the University of Papua in getting to know the campusenvironment. The author conducted research with the title "Creating a 360Virtual Tour Application as a Media for Introducing the Campus Environmentat the University of Papua Using Unity 3D Engine". This application displayspanoramic photos of the buildings and faculties of the University of Papua in360. Based on the research and testing that has been carried out, thisapplication can run well using black box testing. And we hope that thisapplication can help new students when doing PKKMB.